2017
DOI: 10.1016/j.ijhcs.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Gamified crowdsourcing: Conceptualization, literature review, and future agenda

Abstract: Two parallel phenomena are gaining attention in human-computer interaction research: gamification and crowdsourcing. Because crowdsourcing's success depends on a mass of motivated crowdsourcees, crowdsourcing platforms have increasingly been imbued with motivational design features borrowed from games; a practice often called gamification. While the body of literature and knowledge of the phenomenon have begun to accumulate, we still lack a comprehensive and systematic understanding of conceptual foundations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
187
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(198 citation statements)
references
References 144 publications
(365 reference statements)
5
187
1
5
Order By: Relevance
“…Motivated by this debate, Hamari et al analysed 24 empirical studies on gamification and found that, generally, the technique does work, albeit with some caveats that were often to do with positive effects only being found for a particular type of use or user [Hamari et al 2014]. In addition, a review of studies about gamification's use in crowdsourcing found that its use typically leads to an increase in engagement, output quality or other related positive effects [Morschheuser et al 2016], while an extended review supported these findings to show that it increases participation and quality of crowdsourced work [Morschheuser et al 2017]. There is an additional consideration that context may well be key, and that certain systems that rely primarily on rational behaviour are not suited to being gamified [Hamari 2013;Hamari et al 2014].…”
Section: Gamification For Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Motivated by this debate, Hamari et al analysed 24 empirical studies on gamification and found that, generally, the technique does work, albeit with some caveats that were often to do with positive effects only being found for a particular type of use or user [Hamari et al 2014]. In addition, a review of studies about gamification's use in crowdsourcing found that its use typically leads to an increase in engagement, output quality or other related positive effects [Morschheuser et al 2016], while an extended review supported these findings to show that it increases participation and quality of crowdsourced work [Morschheuser et al 2017]. There is an additional consideration that context may well be key, and that certain systems that rely primarily on rational behaviour are not suited to being gamified [Hamari 2013;Hamari et al 2014].…”
Section: Gamification For Engagementmentioning
confidence: 99%
“…Overall, it seems that the attitude towards gamification in citizen science is that it does generally have a positive effect, and as with its use in crowdsourcing, future studies now need to address which specific design choices bring about its success [Morschheuser et al 2017]. As mentioned above, there is an opportunity to further study the introduction of particular game elements to existing projects, following A/B testing or other means, to determine their overall effect on players.…”
Section: Limitations and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, optimizing algorithms of task pricing can greatly enhance the public's participation in the crowdsourcing project. Crowdsourcing implementations are seeking diverse and creative contributions and employing optimization with a richer set of mechanics [15]. Therefore, the issue of task pricing deserved to be researched more deeply.…”
Section: Resultsmentioning
confidence: 99%
“…Gamification has become a popular strategic instrument to engage people in a given activity, to influence behavior and increase performance and productivity in various contexts [12,27,28]. It is one of the major instruments for driving users' motivation in crowdsourcing systems [4], i.e "Transforming Homo Economicus into Homo Ludens" [29].…”
Section: Gamification and Crowdsmentioning
confidence: 99%